Chinua Achebe and the Post-colonial Esthetic: Writing, Identity, and National Formation - Simon Gikandi (Studies in 20th & 21st Century Literature, 1991)
Chinua Achebe is recognized as one of Africa's most important and influential writers, and his novels have focused on the ways in which the European tradition of the novel and African modes of expression relate to each other in both complementary and contesting ways. Achebe's novels are informed by an important theory of writing which tries to mediate the politics of the novel as a form of commentary on the emergence and transformation of nationalism which constitutes the African writer's epistemological context. Achebe's esthetic has been overdetermined by the changing discourse on representation and national identity in colonial and post-colonial Africa. His anxious quest for a post-colonial esthetic is predicated on the belief that narrative can enable the writer to express an alternative order of things opposed to realities imprisoned by imperialism and Western domination.
Keywords: Chinua Achebe; Africa; African; European tradition; novel; expression; modes; complementary; contesting; commentary; emergence; transformation; nationalism; African writer; epistemological; context; esthetic; discourse; national identity; colonial; post-colonial; post-colonial esthetic; narrative; imperialism; Western domination; Western